POTENSI ANTIDIABETIK EKSTRAK ETANOLIK BIJI SALAK (Salacca zalacca) PADA MENCIT PUTIH JANTAN GALUR SWISS (Mus musculus) YANG DIINDUKSI ALOKSAN - Rukminingsih, Fef; Maya Octasari, Paulina; Kristi Nadila, Lilis; Aulia Putri, Fayza (Jurnal Insan Farmasi Indonesia, 2023)
Traditional medicine is an alternative treatment for diabetes mellitus. Flavonoids are compounds that have the activity of lowering blood glucose levels. Snake fruit (Salacca zalacca) contains flavonoids. This study aims to determine the antidiabetic potential of snake fruit ethanolic extract (SFEE) on male white Swiss mice. This research is an experimental study that consisted of 2 stages, namely testing the antidiabetic power and testing the hypoglycemia side effects of SFEE. Each stage was tested on 5 treatment groups. The various doses used were 91 mg, 114 mg, and 137 mg of 20g mice. In stage 1, fasting blood sugar checks are carried out on days 0, 3 and 17. Meanwhile, in stage 2, fasting blood sugar checks are carried out on days 1, 7 and 14. The positive control in the stage 1 test was metformin, while the stage 2 test used glibenclamide. The results showed that varying doses of SFEEÂ  91 mg, 114 mg, and 137 mg of 20g mice had antidiabetic power of 62.87%, 68.07%, and 70.98%. The greater the dose of SFEE, the greater its antidiabetic power. However, the larger the dose of SFEE and the longer it is administered, the hypoglycemic effects will occur